What guides back pain care? A content analysis of low back pain directives in the Australian context - Sarika Parambath; Nathalia Costa; Carmen Huckel Schneider; Fiona M. Blyth (BMC, 2023)
Abstract Background Low back pain (LBP) is a major cause of disease burden around the world. There is known clinical variation in how LBP is treated and addressed; with one cited reason the lack of availability, or use of, evidence-based guidance for clinicians, consumers, and administrators. Despite this a considerable number of policy directives such as clinical practice guidelines, models of care and clinical tools with the aim of improving quality of LBP care do exist. Here we report on the development of a repository of LBP directives developed in the Australian health system and a content analysis of those directives aimed at deepening our understanding of the guidance landscape. Specifically, we sought to determine: (1) What is the type, scale, and scope of LBP directives available? (2) Who are the key stakeholders that drive low back pain care through directives? (3) What content do they cover? (4) What are their gaps and deficiencies? Methods We used online web search and snowballing methods to collate a repository of LBP policy documents collectively called 'directives' including Models of Care (MOC), information sheets, clinical tools, guidelines, surveys, and reports, from the last 20 years. The texts of the directives were analysed using inductive qualitative content analysis adopting methods from descriptive policy content analysis to categorise and analyse content to determine origins, actors, and themes. Results Eighty-four directives were included in our analysis. Of those, 55 were information sheets aimed at either healthcare providers or patients, nine were clinical tools, three were reports, four were guidelines, four were MOC, two were questionnaires and five were referral forms/criteria. The three main categories of content found in the directives were 1. Low back pain features 2. Standards for clinical encounters and 3. Management of LBP, each of which gave rise to different themes and subthemes. Universities, not-for-profit organizations, government organisations, hospitals/Local Health Districts, professional organisations, consumers, and health care insurers were all involved in the production of policy directives. However, there were no clear patterns of roles, responsibilities or authority between these stakeholder groups. Conclusion Directives have the potential to inform practice and to contribute to reducing evidence-policy-practice discordance. Documents in our repository demonstrate that while a range of directives exist across Australia, but the evidence base for many was not apparent. Qualitative content analysis of the directives showed that while there has been increasing attention given to models of care, this is not yet reflected in directives, which generally focus on more specific elements of LBP care at the individual patient and practitioner level. The sheer number and variety of directives, from a wide range of sources and various locations within the Australian health system suggests a fragmented policy landscape without clear authoritative sources. There is a need for clearer, easily accessible trustworthy policy directives that are regularly reviewed and that meet the needs of care providers, and information websites need to be evaluated regularly for their evidence-based nature and quality.